Epidemic outbreak of candidemia caused by unusual types of Candida non-albicans: clinical course patterns and search for the source - I. I. Kalinina; D. V. Litvinov; I. V. Veselova; N. I. Ponomareva; L. N. Shelikhova; V. V. Fominykh; G. A. Klyasova; A. A. Maschan (Онкогематология, 2014)
Introduction: Invasive fungal infections (IFI) remain an unresolved issue of hematology/oncology despite the introduction of methods of early diagnostic and invent of new highly active antimycotics. In etiologic structure of IFI the leading role belongs to candidiasis, the most frequent clinical form of which is candidemia. Candidemias in the pediatric hematology/oncology departments usually occur as sporadic cases, and epidemics are very rare. We describe an epidemic outbreak of candidemia caused by species of Candida non-albicans rarely reported in patients.Results: Ten cases of candidemia were registered in the hematology/oncology department within one month. Candidemia was caused by C. guilliermondi in 4 patients (in 1 concomitantly with C. calliculosa), by С. parapsilosis – in 3 patients and by C. pelliculosa in another 3 patients. Contaminated intravenous 4 % KCl solution has been found to be the source of candidemia. In four patients granulocytes count was < 0.5  109/l at the time of positive blood cultures. Clinical manifestation of candidemia included fever > 38.5 in all patients and lung involvement in 2 patients. All patients received systemic antifungal therapy: 5 — monotherapy, 3 — combinations of 2 drugs and 2 — of 3 drugs. Central venous catheter was removed in 4 patients. Clinical and microbiological cure was achieved in all patients; the mortality rate was 0 %. In 2 patients candidemia relapsed 22 and 60 days after the first episode.Conclusions: Outbreaks of systemic infections caused by unusual pathogens necessitate searching of a single infection source. Candidemia caused by a direct pathogen inoculation in the bloodstream, in the absence of multiple risk factors for invasive fungal infections follows a favorable course.